Peripheral Helper T Cell Responses in Human Diseases - Yoshitomi, Hiroyuki (Frontiers in Immunology, 2022)
A series of rheumatoid arthritis (RA) studies established a PD-1hiCXCR5-CD4+ T-cell subset that was coined peripheral helper T (Tph) cells. CXCL13 production is a key feature of Tph cells and may contribute to the formation of tertiary lymphoid structures (TLS) in inflamed tissues. In addition, Tph cells provide help to B cells in situ as efficiently as follicular helper T (Tfh) cells, and these features would implicate Tph cells in the pathogenesis of RA. Subsequent studies have revealed that Tph cells are involved in various human diseases such as autoimmune diseases, infectious diseases, and cancers. Although the analysis of human immunity has various limitations, accumulating evidence demonstrated the expansion of B cells with low somatic hypermutation and a link between TLS and immune functions in these diseases. We discuss about the emerging roles of the Tph cell and its relevant immune responses in peripheral tissues including B-cell expansion with atypical features.